Feline immunodeficiency virus vectors persistently transduce nondividing airway epithelia and correct the cystic fibrosis defect - Wang, Guoshun (American Society for Clinical Investigation, 1999)
Several problems limit the application of gene transfer to correct the cystic fibrosis (CF) Cl(–) transport defect in airway epithelia. These include inefficient transduction with vectors applied to the apical surface, a low rate of division by airway epithelial cells, failure of transgene expression to persist, and immune responses to vectors or vector-encoded proteins. To address these issues, we used a feline immunodeficiency virus–based (FIV-based) vector. FIV vector formulated with a calcium chelator transduced fully differentiated, nondividing human airway epithelia when applied to the apical surface. FIV-based vector encoding the cystic fibrosis transmembrane conductance regulator cDNA corrected the Cl(–) transport defect in differentiated CF airway epithelia for the life of the culture (>3 months). When this approach was applied in vivo, FIV vector expressing β-galactosidase transduced 1–14% of adult rabbit airway epithelia. Transduced cells were present in the conducting airways, bronchioles, and alveoli. Importantly, gene expression persisted, and cells with progenitor capacity were targeted. FIV-based lentiviral vectors may be useful for the treatment of genetic lung diseases such as CF. This article may have been published online in advance of the print edition. The date of publication is available from the JCI website, http://www.jci.org. J. Clin. Invest. 104:R55–R62 (1999).